Empowering of School Committees: Concrete Steps to Improve The Quality of Education - Maula, Faradina Milla; Noviyanti, Shobihatul Fitroh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to analyze the importance of school committees' role and strategies in improving education quality. Through comprehensive analysis, this research identifies the role and strategies of school committees in developing school programs and supporting and inhibiting factors in the implementation process. This research uses a qualitative case study type approach. Data was collected through semi-structured interviews, observation and documentation to determine the role and strategies of influential school committees in efforts to improve school quality. The research results illustrate that the school committee plays an active role as a school partner in supporting school quality improvement initiatives. The strategy implemented by the school committee is carried out through continuous evaluation, recommendations, and raising resources to find problems, take corrective action, and optimize available resources. This research highlights that the success of the school committee's role and strategy will be much more optimal and maximal if it is linked to quality improvements that all parties, both internal and external to the school recognize. This research contributes to advancing school quality improvement methods that can be used and developed in madrasah and schools in the future.